How to succeed at university : an essential guide to academic skills and personal development - Smale, Bob; Fowlie, Julie (SAGE Publications, 2009)
A structured and supportive approach to developing a student's learning and achievement. The bookhelps the reader plan for their own personal, educational and career development.